Determine the fishing season of scad (Decapterus sp.) landed at Pusong Fish Landing Base, Lhokseumawe, Indonesia - Alvi Rahmah; Salsadira Dwi Zani; Makwiyah A Chaliluddin; A A Muhammadar; Sayyid Afdhal El Rahimi (Depik, 2022)
The scad (Decapterus sp.) is one species commonly caught using purse seine and landed at the Pusong Fish Landing Base, Lhokseumawe, Aceh. The fishermen at this site do not have accurate knowledge about the fishing season of the scad, which leads them to miss out on peak fish catching season and increases the ambiguity about the fish landing data. The goal of this research is to compute the trend of Catch Per Unit Effort (CPUE) for scad fisheries over the last five years (2013-2017) and to examine the fishing season trends of scad landed at Pusong fish landing base. This study took place at the Pusong Fish Landing Base in August 2020. The moving average approach was used to process catch data from 2013 to 2017. Primary and secondary data about scad production and number of fishing trips were used to compile the research findings. The results showed that the CPUE for purse seine catch landed at Pusong Fish Landing Base varies from year to year. The highest CPUE value was recorded in 2015 with 442,534 kg/trip, and the lowest was in 2013 with a value of 27,674 kg/trip. The fishing season index for Scad (Decapterus sp.) has a high rating, indicating that this fish species can be caught all year. Based on the fishing season identification criteria, the fishing season index value greater than 100% indicates the peak season. Results from this research indicate that the peak season for scad landed at Pusong Fish Landing Base occurs in July, August, September, October, and November, with their index values of 151%, 146%, 119%, 122%, and 126% respectively. A fishing season index score of less than 100% indicates low season, this was recorded for January, February, March, April, May, June, and December (48%, 97%, 57%, 90%, 62%, 86% and 97%).Keywords:ScadFishing Season IndexCPUE